Caribou Hunters and Researchers at the Co-management Interface: Emergent Dilemmas and the Dynamics of Legitimacy in Power Sharing - Kofinas, Gary P. (Anthropologica, 2022)
A crisis involving indigenous knowledge, caribou science and proposed oil development illustrates the dynamics of legitimacy in formal co-management. Co-management, while typically framed as an institution for power sharing, was also a force of change that affected the values and actions of those involved. Crisis conditions led hunters to express dissatisfaction to their co-management board, forcing board members to work towards regional consensus, which in turn led to a change in community perspectives. Co-management decision makers with multiple affiliations faced difficult dilemmas while seeking to maintain cultural traditions, protect sensitive wildlife habitat, and manage for the legitimacy of their co-management process.